Mali : Poverty and Gender Notes - World Bank (Washington, DC, 2013)
Mali is one of the poorest countries in the world, with a gross domestic product (GDP) per capita of about $ 691 in 2010. Mali's steady per capita GDP growth was accompanied with a significant decline in the poverty rate, from 55.6 percent in 2001 to 43.6 percent in 2009-10. Mali's rapid population growth still has led to an increase of the overall number of people living in poverty, and is constraining progress in terms of per capita health and education outcomes. High fertility rates and gender imbalances are key drivers of Mali's poverty dynamics. The present report compiles three different notes, emphasizing the interrelation between poverty, demographics and gender imbalances. The first note discusses the evolution of poverty in Mali since 2001. The second note reviews recent demographic trends and related policies. The third note reports on the latest available data on females in business and employment within the formal sector. The compilation of these three notes aims to stimulate debates and the exploration of policy options to tackle poverty through its interactions with fertility and gender imbalances. It also highlights conclusion of each note.